2010
DOI: 10.3354/ab00249
|View full text |Cite
|
Sign up to set email alerts
|

Control of dissolved oxygen in northern temperate lakes over scales ranging from minutes to days

Abstract: Dissolved oxygen (DO) observations from in situ sensors show complex temporal patterns, suggesting that the balance of control by underlying processes changes across scales. At scales ranging from minutes to days, a number of physical and biological processes, such as internal waves, mixing, and ecosystem metabolism, may impart pattern on observed DO. In discriminating the control over DO variability by scale, this helps us to reduce uncertainty in estimates of important ecosystem rates, such as gross primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 30 publications
(32 reference statements)
1
17
0
Order By: Relevance
“…A full treatment of how other nondeterministic drivers of normalO2‐dynamics affect diel oxygen methods is out of the scope of this manuscript, but we believe that further analysis will contribute to a increased understanding of how the different scales of the deterministic and nondeterministic parts of normalO2‐dynamics affect estimates of metabolism. This is a topic that has not received a lot of attention [ see , however, Langman et al (); Coloso et al ()].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A full treatment of how other nondeterministic drivers of normalO2‐dynamics affect diel oxygen methods is out of the scope of this manuscript, but we believe that further analysis will contribute to a increased understanding of how the different scales of the deterministic and nondeterministic parts of normalO2‐dynamics affect estimates of metabolism. This is a topic that has not received a lot of attention [ see , however, Langman et al (); Coloso et al ()].…”
Section: Discussionmentioning
confidence: 99%
“…Kester et al () already demonstrated that the spectral analysis of oxygen time series data can provide relevant information on the different processes that affect the oxygen dynamics in natural waters. More recently, Coloso et al () and Langman et al () applied wavelet techniques to separate the normalO2‐dynamics at different time scales. Here, we elaborate this idea by combining the diel oxygen method with spectral analysis.…”
mentioning
confidence: 99%
“…Mixing driven by wind or heat loss can alter observed DO concentrations by transporting water masses with different DO concentrations past a sensor. In a recent study exploring short-term variability in high frequency DO measurements, wind was consistently related to DO variability over short time periods in scales ranging from minutes to hours (Langman et al 2010).…”
mentioning
confidence: 97%
“…The Linear Model (LM) is similar to the simple model described in Hanson et al (2008) in that it fits parameters to the DO time series and includes a term accounting for error in the modeled process. Models such as LM use fitted parameters and are common in metabolism studies (Staehr and Sand-Jensen 2006;Hanson et al 2006;Van de Bogert et al 2007;Langman et al 2010), and contrast with the bookkeeping approach in that they include an error term, instead of subsuming the error in the estimates of the metabolism parameters. The third model makes use of a Kalman filter, an approach that is well established in statistics (Kalman 1960;Harvey 1989).…”
Section: Modelsmentioning
confidence: 99%